Piwi Is a Key Regulator of Both Somatic and Germline Stem Cells in the Drosophila Testis - Jacob Gonzalez; Hongying Qi; Na Liu; Haifan Lin (Cell Reports, 2015)
The Piwi-piRNA pathway is well known for its germline function, yet its somatic role remains elusive. We show here that Piwi is required autonomously not only for germline stem cell (GSC) but also for somatic cyst stem cell (CySC) maintenance in the Drosophila testis. Reducing Piwi activity in the testis caused defects in CySC differentiation. Accompanying this, GSC daughters expanded beyond the vicinity of the hub but failed to differentiate further. Moreover, Piwi deficient in nuclear localization caused similar defects in somatic and germ cell differentiation, which was rescued by somatic Piwi expression. To explore the underlying molecular mechanism, we identified Piwi-bound piRNAs that uniquely map to a gene key for gonadal development, Fasciclin 3, and demonstrate that Piwi regulates its expression in somatic cyst cells. Our work reveals the cell-autonomous function of Piwi in both somatic and germline stem cell types, with somatic function possibly via its epigenetic mechanism.